KAUSALITAS UPAH MINIMUM REGIONAL DENGAN LAJU INFLASI DI PROVINSI D.I. YOGYAKARTA - Azis, Mohammad Khaerul; Wibowo, Muhammad Ghafur (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2016)
This study aims to analyze the causal relationship between the regionalminimum wage (UMR) with the rate of infl ation, as well as long-term relationship of two variables. Several previous studies have said that there is a unidirectional relationship, both infl ation affect UMR, or UMR affecting infl ation. There was even a study that found that there is a two-way (reciprocal) between the two. In this study, an analysis tool used is the Vector Autoregression (VAR). From the results, it can be concluded that the relationship between the minimum wage to infl ation in the province of DIY is a unidirectional relationship, where infl ation affects the amount of the minimum wage set. These results indicate that the regional minimum wage stipulatedin Yogyakarta province has been in accordance with the principles of remuneration within the perspective of Islamic Economics as one of the considerations in setting is infl ation. Thus, the element of appropriateness as one element in remuneration are met. Through the study also concluded that the regional minimum wage (UMR) with contained infl ation long-term relationship.